PENERAPAN MODEL PEMBELAJARAN BERBASIS LINGKUNGAN UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR SISWA - Zaituni (UNIB Press, 2024)
This study aims to: describe the application of environmental-based learning models to increase student participation in learning the basics of plant cultivation for class XI students of APT SMK Negeri 2 Mukomuko, describe the application of environmental-based learning models to improve student achievement in learning the basics of plant cultivation student XI APT SMK Negeri 2 Mukomuko. This research was conducted using Classroom Action Research. The subjects of this study were students of class XI Agribusiness Plant Production (APT) SMK Negeri 2 Mukomuko which consisted of 11 students. This study uses a total sample and data collection is done by observation and test sheets. The data obtained were analyzed based on the type of data where qualitative data were analyzed descriptively and quantitative data were analyzed quantitatively using the average formula and t-test. Based on the results of research carried out for three cycles, the results of the analysis show that the ability of teachers to apply the learning model has increased during its application, student participation has also increased from the first cycle to the third cycle, in addition, student learning achievement has increased significantly from the first cycle to the third cycle. third. The conclusions of this study are: (1) the application of the environment-based learning model can increase student participation, (2) the application of the environment-based learning model can improve student learning achievement